K-theory - International Meeting on K-theory; International meeting on K-theory Strasbourg, France 29 Jun - 3 Jul 1992 (Societe Mathematique de France, 1994)
This volume contains the contributions by some of the participants of the International Meeting on K-Theory which was held from June 29 th to July 3rd 1992 at the Institut de Recherche Math
Keywords: Algebra; K-theory; Topology